Life span motor development - Haywood, Kathleen (Human Kinetics, 2009)
Uses the model of constraints (or dynamical systems) approach in discussing reasons for changes in movement throughout the life span. This title encourages students to observe and examine how the interactions of the individual, environment, and task affect changes in a person's movements.